Influence of fiber content on mechanical and morphological properties of woven kenaf reinforced PVB film produced using a hot press technique - Salman, Suhad Dawood; Leman, Zulkiflle; Hameed Sultan, Mohamed Thariq; Ishak, Mohamad Ridzwan; Cardona, Francisco (Hindawi Publishing Corporation, 2016)
This work addresses the results of experimental investigation carried out on mechanical and morphological properties of plain woven kenaf fiber reinforced PVB film which was prepared by hot press technique. The composites were prepared with various fiber contents: 0%, 10%, 20%, 30%, 40%, 50%, and 60% (by weight), with the processing parameters 165°C, 20 min, and at a pressure of 8 MPa applied on the material. Tensile, flexural, and Charpy impact properties were studied as well as morphological properties of impact fracture surface. With the increase in kenaf fibers content up to 40%, the PVB composites have shown lower tensile and flexural strength accompanied with reduction in the ultimate strain of the composite. The results showed that impact properties were affected in markedly different ways by using various kenaf contents and decrease with the increase in kenaf fiber content up to 40%; however, high impact strength was observed even with 40% kenaf fiber content. Furthermore, scanning electron microscopy for impact samples was utilised to demonstrate the different failures in the fracture surfaces for various kenaf fibers contents.